Preventing pest plagues - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Mackson Banda, Deputy Director of Agricultural Research in Malawi on how farmers and policies are working to stop cotton pests spreading in the country.